STABILISASI LEMPUNG BANDUNG DENGAN LIMBAH INDUSTRI GAS KARBIT - Halim Hasmar, Abdul
Waste product from carbide gas industry, based on laboratory analysis, is a waste containing lime (CaO) 66.18 percent obtained from waste sample at age one week and one year. Bandung clay used in this research was taken from the depth of 1 to 1.5 metre at km 33.5 South of Padalarang-Cileunyi Toll Road. The clay used in this investigation has a specific gravity of 2.5242; water content of 71.44 percent; liquid limit of 86.88 percent; plastic limit of 27.51 percent; plasticity index of 59.37 percent and 96.37 percent of material passing number 200. At the mixture of waste and clay with the ratio 0, 2, 4, 6, 8 and 10 percent, the maximum compressive strength achived at ratio of 6 percent which was 3.851 kg/cm2, and was 35.27 percent higher than strength of sample without waste (ratio 0 percent). At this optimum condition, swelling potential and swelling pressure were zero, the plasticity index decrease by 99.11 percent of the plasticity index of the original clay. At the consolidation test, the result is that the waste ratio was a funtion of compression index (Cc). The durability test of the optimum waste for curing time 7 days, qu increased by 79.03 percent, whereas for 7 to 14 days, 14 to 21 days, 21 to 28 days, 28 to 35 days and 35 to 42 days, the durability ratio increased by 2.33 percent, the relationship is almost horizontal. At the mixture of lime and clay at the optimum waste (6 percent) at curing time 7 days, the compressive strength was 11.87 percent lower than that of mixture of clay and waste. For the mixture made with clay and lime at curing time 14 days the compressive strength was 0.55 percent lower than that of the mixture of clay and waste, and at curing time 21 days the corresponding value was 10.89 percent. According to Atterberg limits test result, the mixture made with clay and waste of carbide gas industry had better ability to reduce plasticity index than the mixture of clay and lime.